2003
DOI: 10.1103/physrevb.68.155317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an additional infrared excitation on the luminescence efficiency of a single InAs/GaAs quantum dot

Abstract: Microphotoluminescence ͑PL͒ spectra of a single InAs/GaAs self-assembled quantum dot ͑QD͒ are studied under the main excitation of electron-hole pairs in the wetting layer ͑WL͒ and an additional infrared ͑IR͒ laser illumination. It is demonstrated that the IR laser with fixed photon energy well below the QD ground state induces striking changes in the spectra for a range of excitation energies and powers of the two lasers. For the main excitation above a threshold energy, defined as the onset of transitions be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 49 publications
2
54
0
Order By: Relevance
“…For larger C-doping densities, the QD occupancy increases more slowly with increasing n A , while at the same time the depletion length rapidly decreases below it maximum value. For the typical acceptor densities of the order of 10 13 − 10 14 cm −3 [58], the QD is nearly populated by three holes, which is more than the two holes occupancy considered in our work hypothesis (see section IV A). However, excepting an average value of the typical acceptor densities, we do not have a precise knowledge of the C-doping in the QD vicinity.…”
Section: Discussionmentioning
confidence: 89%
“…For larger C-doping densities, the QD occupancy increases more slowly with increasing n A , while at the same time the depletion length rapidly decreases below it maximum value. For the typical acceptor densities of the order of 10 13 − 10 14 cm −3 [58], the QD is nearly populated by three holes, which is more than the two holes occupancy considered in our work hypothesis (see section IV A). However, excepting an average value of the typical acceptor densities, we do not have a precise knowledge of the C-doping in the QD vicinity.…”
Section: Discussionmentioning
confidence: 89%
“…The distance between the dots is consequently smaller than the diffusion length of the photoinduced carriers. Our previous study revealed an exciton diffusion length in the WL of approximately 1 m. 7 Since only a very limited WL contribution can be observed in the low-temperature PL spectrum, we roughly estimate a dot separation of about 1 m and a dot density of approximately 10 8 cm −2 .…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work based on lateral electric field dependence studies on single dot related PL indicates a depth of the potential fluctuations of approximately 3 meV. 14 Furthermore, PLE measurements reveal a Stokes shift of about 5 meV, 7,15 which also gives a rough estimate of the depth of the local WL potential fluctuations. Based on these different experimental observations, the depth of the WL potential fluctuations is estimated to be 3 -5 meV.…”
Section: Figmentioning
confidence: 99%
“…11,12 In contrast to single laser excitation, which only results in X 0 , when adding a second infrared ͑IR͒ laser excitation X + is formed, as was demonstrated by us earlier. 13 An even higher polarization is measured for X + , c =73%, which is considered to be an upper bound for spin polarization of electrons captured into the QD from the wetting layer ͑WL͒.…”
Section: Manipulating the Spin Polarization Of Excitons In A Single Qmentioning
confidence: 99%
“…Detailed descriptions of the sample and of the experimental setup are given elsewhere. [11][12][13] c was determined as c = ͑I co − I cross ͒ / ͑I co + I cross ͒, where I co ͑I cross ͒ corresponds to the spectrally integrated PL signal of the co͑cross-͒circular components.…”
Section: Manipulating the Spin Polarization Of Excitons In A Single Qmentioning
confidence: 99%